2011
DOI: 10.1037/a0023511
|View full text |Cite
|
Sign up to set email alerts
|

Spatial biases in peripersonal space in sighted and blind individuals revealed by a haptic line bisection paradigm.

Abstract: Our representation of peripersonal space does not always accurately reflect the physical world. An example of this is pseudoneglect, a phenomenon in which neurologically normal individuals bisect to the left of the veridical midpoint, reflecting an overrepresentation of the left portion of space compared with the right one. Consistent biases have also been observed in the vertical and radial planes. It is an open question whether these biases depend on normal visual experience for their occurrence. Here we sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 61 publications
(149 reference statements)
8
31
1
Order By: Relevance
“…Leftward biases also occur in lighting of artwork (Sun & Perona, 1998) and in advertisements (Thomas, Burkitt, Patrick, & Elias, 2008) and advertisement lighting preferences (Hutchison, Thomas, & Elias, 2011). In line bisection, humans make leftward bisection errors in pen-and-paper tasks (MacDonald-Nethercott, Kinnear, & Venneri, 2000;McCourt, 2001) as well as in haptic bisection tasks (Cattaneo, Fantino, Tinti, Pascual-Leone, Silvanto, & Vecchi, 2011), while young chickens (Gallus gallus domesticus) also make leftward errors while pecking at lines of beads (Regolin, 2006). The role of reading and writing direction of an individual's fi rst language (native reading direction) in cognitive tasks has not yet been agreed upon.…”
mentioning
confidence: 99%
“…Leftward biases also occur in lighting of artwork (Sun & Perona, 1998) and in advertisements (Thomas, Burkitt, Patrick, & Elias, 2008) and advertisement lighting preferences (Hutchison, Thomas, & Elias, 2011). In line bisection, humans make leftward bisection errors in pen-and-paper tasks (MacDonald-Nethercott, Kinnear, & Venneri, 2000;McCourt, 2001) as well as in haptic bisection tasks (Cattaneo, Fantino, Tinti, Pascual-Leone, Silvanto, & Vecchi, 2011), while young chickens (Gallus gallus domesticus) also make leftward errors while pecking at lines of beads (Regolin, 2006). The role of reading and writing direction of an individual's fi rst language (native reading direction) in cognitive tasks has not yet been agreed upon.…”
mentioning
confidence: 99%
“…The aim of this study was to shed further light on this issue. In a prior study by our group carried out in sighted participants, we found that hand movements performed in the left peripersonal space (irrespective of the hand used) accentuated underestimation (i.e., a leftward bias) in numerical bisection, whereas movements in the right peripersonal space (irrespective of hand used) had the opposite tendency (Cattaneo, Fantino, Silvanto, Vallar, & Vecchi, 2011). These results suggest that the correspondence between physical space and the mental number space in sighted individuals is anchored to a world-based reference frame centered on the participants’ body (i.e., left in physical space and left on the mental number line).…”
Section: Introductionmentioning
confidence: 64%
“…The experimental task consisted of a numerical bisection paradigm that has been used in a number of prior studies to investigate spatial attentional biases in numerical representation (e.g., Cattaneo, Fantino, Silvanto, Tinti, & Vecchi, 2011; Göbel, Calabria, Farnè & Rossetti, 2006; Loftus, Nicholls, Mattingley, Chapman & Bradshaw, 2009). Participants were verbally presented with a total of 80 different pairs of three-digit numbers; half in ascending (e.g., “117 166”) and half in descending order (e.g., “959 934”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations